Analisis Kesulitan Belajar Operasi Hitung Pembagian pada Siswa Kelas IV SDN Cideng 09: Analysis of Learning Difficulties in Arithmetic Operations of Division in Grade IV Students of SDN Cideng 09 - Pujiarti; Manurung, Alberth Supriyanto (ITScience (Information Technology and Science), 2024)
Mathematics in formal learning is one of the most important subjects taught to measure students' thinking skills in arithmetic. Students' difficulties in completing arithmetic operations can be caused by the imperfection of the mathematics learning process in class. This study aims to describe the difficulties in learning the arithmetic operation of division in grade IV students of SDN Cideng 09. The method used in qualitative research tends to obtain written or verbal descriptions of the attitudes of the community or real research objects, while in quantitative research, inductive data analysis is used, and researchers and informants are brought closer during data collection. This presentation will refer to the findings of a field study regarding learning challenges in grade IV students of SDN Cideng 09 and discuss the results of the instrument consisting of essay questions and several interviews. At SDN Cideng 09, one of the educators expressed his concern that grade IV students had difficulty understanding the concept of division. It seems that many students in this class have difficulty in mathematics, especially in division. The findings of this study reveal that a number of grade IV students of SDN Cideng 09 have difficulty understanding the basic concept of division. Finding solutions to division problems with multiplication will not be a problem for students if they truly understand division as repeated subtraction.